Chaotic Dynamics and Stability of Liposomal Nanosystems - Naziris, Nikolaos; Chountoulesi, Maria; Stavrinides, Stavros; Hanias, Michael; Demetzos, Costas (Current Nanoscience, 2022)
Background: Natural and living systems are dynamical systems that demonstrate complex behavior, which appears to be deterministic chaotic, characterized and governed by entropy increase and loss of information throughout their entire lifespan. Lipidic nanoparticles, such as liposomes, as artificial biomembranes, have long been considered appropriate models for studying various membrane phenomena that cell systems exhibit. By utilizing these models, we can better comprehend cellular functions, stability, as well as factors that might alter the cell physiology, leading to severe disease states. In addition, liposomes are well-established drug and vaccine delivery nanosystems, which are present in the market, playing a significant role; therefore, due to their importance, issues concerning their effectiveness and stability are research topics that are constantly investigated and updated. Methods: In this study, the emergent deterministic chaotic behavior of liposomes is described, while evaluation in accordance to their colloidal physical stability, by utilizing established nonlinear dynamics tools, is presented. Two liposomes of different composition and physical stability were developed and a chaotic evaluation on the time series of their size and polydispersity was conducted. Results: The utilized models revealed instability, loss of information and order loss for both liposomes in due time, with important differentiations. An initial interpretation of the results is apposed, whereas the foundations for further investigating possible exploitation of the demonstrated nonlinearity and adaptability of artificial biomembranes is laid, with projection on biosystems. Conclusion: The present approach is expected to impact the application of lipidic nanoparticles and liposomes in various crucial fields, such as drug and vaccine delivery, providing useful information for both the academia and industry.
Keywords: Liposomes